2018
DOI: 10.1101/286815
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Lost in translation: egg transcriptome reveals molecular signature to predict developmental success and novel maternal-effect genes

Abstract: BackgroundGood quality or developmentally competent eggs result in high survival of progeny. Previous research has shed light on factors that determine egg quality, however, large gaps remain. Initial development of the embryo relies on maternally-inherited molecules, such as transcripts, deposited in the egg, thus, they would likely reflect egg quality. We performed transcriptome analysis on zebrafish fertilized eggs of different quality from unrelated, wildtype couples to obtain a global portrait of the egg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1
1
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 63 publications
1
5
0
Order By: Relevance
“…In addition, we found that the foxr1 mutant-derived eggs were non-cellularized and did not undergo subsequent cell division despite being fertilized, as also observed for eggs derived from npm2b mutant females [26]. This suggested that their defect did not lie in the capability to be fertilized, as seen in slc29a1a and otulina mutants [3], In this study, we showed that foxr1 is found in a wide-range of vertebrates and is homologous to the foxr1 genes found in other species. In teleosts, foxr1 expression is found predominately in the ovary while in mammals, it appears to be specific to the male germline…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…In addition, we found that the foxr1 mutant-derived eggs were non-cellularized and did not undergo subsequent cell division despite being fertilized, as also observed for eggs derived from npm2b mutant females [26]. This suggested that their defect did not lie in the capability to be fertilized, as seen in slc29a1a and otulina mutants [3], In this study, we showed that foxr1 is found in a wide-range of vertebrates and is homologous to the foxr1 genes found in other species. In teleosts, foxr1 expression is found predominately in the ovary while in mammals, it appears to be specific to the male germline…”
Section: Discussionsupporting
confidence: 58%
“…Maternal-effect genes are transcribed from the maternal genome and encode the maternal factors that are deposited into the developing oocytes in order to coordinate embryonic development before MBT [2]. We had previously explored the zebrafish egg transcriptome [3] and proteome [4] in order to gain further understanding of the maternal factors that contribute to good quality or developmentally competent eggs that result in high survival of progeny. However, despite the increasing identification of maternal-effect genes and their functions, large gaps still remain especially the role of genes that regulate early embryogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Maternal-effect genes are transcribed from the maternal genome and encode the maternal factors that are deposited into the developing oocytes in order to coordinate embryonic development before MBT ( Lindeman & Pelegri, 2010 ). We had previously explored the zebrafish egg transcriptome ( Cheung et al, 2018 ) and proteome ( Yilmaz et al, 2017 ) in order to gain further understanding of the maternal factors that contribute to good quality or developmentally competent eggs that result in high survival of progeny. However, despite the increasing identification of maternal-effect genes and their functions, large gaps still remain especially the role of genes that regulate early embryogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Further, we found that the foxr1 mutant-derived eggs were non-cellularized and did not undergo subsequent cell division despite being fertilized. This suggested that their defect did not lie in the capability to be fertilized, as seen in slc29a1a and otulina mutants [3], but in the cell cycle and proliferation processes. Thus, we investigated the expression profiles of p21 , p27 , and rictor , which are all cell cycle and cell survival regulators, since Santo et al had previously knocked down foxr1 using short hairpin RNAs in mammalian cells and found it to be a transcriptional repressor of them[26].…”
Section: Discussionmentioning
confidence: 99%
“…Maternal-effect genes are transcribed from the maternal genome and encode the maternal factors that are deposited into the developing oocytes in order to coordinate embryonic development before MBT [2]. We had previously explored the zebrafish egg transcriptome [3] and proteome [4] in order to gain further understanding of the maternal factors that contribute to good quality or developmentally competent eggs that result in high survival of progeny. However, large gaps still remain.…”
Section: Introductionmentioning
confidence: 99%